THE ASSESSMENT OF KNOWLEDGE, ATTITUDE AND PRACTICE OF ANTIBIOTICS USAGE AMONG SAUDI FEMALE STUDENTS IN PRINCESS NOURAH UNIVERSITY (PNU) - Barakh, Njood; Algain, Suha; Barrak, Alhanouf; Mazrooa, Sara; Alfaleh, Sumaiah; Alotaibi, Felwah; Mohamed, N (LIFE: International Journal of Health and Life-Sciences, 2016)
Background: Antibiotic misuse is one of the biggest major health problems worldwide. Awareness and good practice of antibiotic usage among females has a great influence to build-up in the healthy community. In this study, we analyzed the present status of Princess Nourha University (PNU) students’ knowledge, attitude, and practice (KAP) on the usage of antibiotics, and examined the influence of PNU medical curriculum on the appropriate usage of antibiotics among medical students. Objectives: to investigate the knowledge, attitude and behavior of PNU students (Medical and non-medical) in relation of the awareness of using antibiotics. Materials and Methods: In this study, a cross-sectional survey was conducted in Riyadh city. A total of 394 female students from PNU, aged 18-24 years, enrolling in medical school (M) and non-medical school (NM) were chosen as the subject of study. Respondents were surveyed to assess their knowledge, attitude and practice toward antibiotic usage. Results: 77% of M has a good knowledge of the types of antibiotics whereas 36.6% of NM was unable to differentiate between antibiotics and pain-killers. A closely similar percentage of M (85.1%) and NM (81.0%) disagreed the universal principles of antibiotic use is not wide enough. A total of 96.3% of M and 97.2% of NM agreed that human body contains health-beneficial bacteria. Lastly, 77.6% of M and 74.9% of NM believed that newer and more expensive antibiotics would have better effect. The correlation in antibiotic usage without doctor’s instruction by medical students is highly significant (p<0.001). Conclusions: It is essential to develop educational interventions to correct the misuse and misunderstanding of antibiotics to be able to have a health educated community.